Analisis Faktor-Faktor Mempengaruhi Implementasi Kebijakan Peraturan Daerah Nomor 8 Tahun 2017 Tentang Kawasan Tanpa Rokok (KTR) di SMK 6 Kota Samarinda - Juliana Hasibuan; Ratno Adrianto; Nur Rohmah; Ike Anggraini G; Irfansyah Bahruddin Pakki; Ayu Indira Dwika Lestari (Universitas Pahlawan Tuanku Tambusai, 2025)
Indonesia is currently facing a growing number of active smokers, particularly among adolescents. In an effort to protect the public from the negative impacts of cigarette smoke, the Government has established a Smoke-Free Area (KTR) policy. This study aims to analyze the factors influencing the implementation of Regional Regulation Number 8 of 2017 concerning Smoke-Free Areas (KTR) at SMK Negeri 6 Samarinda.This research employed a quantitative approach with a cross-sectional design. The sampling technique used was stratified random sampling, involving 428 student respondents. Data were collected using a questionnaire, and analyzed using path analysis with the help of SPSS software.The results show a direct influence of communication, bureaucratic structure, resources, and disposition on policy implementation (each with a p-value = 0.000). Furthermore, communication had a direct effect on resources (p-value = 0.000), and bureaucratic structure had a direct effect on disposition (p-value = 0.000). An indirect effect was also found between communication and implementation through resources (Sobel test value = 6.132 > t-table = 1.969), as well as between bureaucratic structure and implementation through disposition (Sobel test value = 8.625 > t-table = 1.969).In conclusion, communication, resources, bureaucratic structure, and disposition are key factors influencing the implementation of Regional Regulation No. 8 of 2017 on Smoke-Free Areas in the school environment. communication needs to be improved through regular and interesting socialization. Keywords: Implementation, Smoke-Free Areas, Adolescents, School, Smoking